ANALISIS RASIO LIKUIDITAS, PROFITABILITAS DAN PERPUTARAN PERSEDIAAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mainisa, Erni; Marlina Br. Purba, Neni (EDUTECH CONSULTANT, 2020)
The purpose of this research is find out the analysis of effect of liquidity ratio (Current Ratio), profitability ratio (ROA) and inventory turnover to assess the value of company. In this study, data used are secondary data derived from company's financial statements, and used many as 17 companies out of 111 objects are retail trade, service, and investment companies listing on Indonesia Stock Exchange in the 2014-2018 period. Data collection techniques used in form of documentation techniques. Data processing technique used data processing with SPSS version 21. Data analysis method used multiple linear regression. Results of T test show that partially Current Ratio has a negative and significant effect on firm value, while ROA and inventory turnover have a positive and significant effect on firm value. Results of F test analysis indicate that variable Liquidity Ratio, Profitability and Inventory Turnover together have a significant effect on firm value.